Autoavaliação Institucional Participativa na Educação Infantil: para além dos dados levantados - Egi, Carla Matie de Jesus (2023)
This research has os its object of study the Participatory Institutional Self-Assessment in Early Childhood Education: analysis and uses of the data collected in three Early Childhood Education units of the Municipal Network of São Paulo, aiming to answer the following problematization: How are the data collected in the institutional self-assessment used in the School Unit? The general objective is to understand how the school community analyzes the data collected in the institutional self-assessment and uses them in the planning of actions aimed at the quality of care of babies and children. As specific objectives were listed: to identify how the units use the data collected in the self-assessment and how they appear in the PPP; analyze how the data are used in the qualification of the unit's work; point out the similarities and/or differences in the application, as well as in the analysis and use of data by the three units. It starts from the premise that external demands are prioritized and what concerns the children's daily life, the power of the instrument, remains in the background. The research universe is composed of three Early Childhood Education Units in the City of São Paulo, being a Direct Early Childhood Education Center, a Partner Early Childhood Education Center and a Municipal Early Childhood Education School. The research participants are a manager, a teacher, a representative of the support staff, a family representative and a child (when there are Mirim Indicators) of each School Unit. As a theoretical reference, we highlight the categories and respective theorists of the quality of Early Childhood Education: Maria Malta Campos, Anna Bondioli, Gunilla Dahlberg, Peter Moss and Alan Pence, Participation and Negotiated Quality: Anna Bondioli, Paulo Freire, Institutional Assessment Adilson Dalben, Mara Regina Lemes de Sordi, Egle Becchi, Anna Bondioli, Official Documents: National Quality Parameters for Early Childhood Education (2008), Quality Indicators of Early Childhood Education (2009), Basic Quality Standards of Early Childhood Education from São Paulo (2015), Quality Indicators for Early Childhood Education from São Paulo (2016). The methodology is a qualitative intervention research inspired by the cartography method and the data production instruments are the participant observation in the Quality Indicators application meeting and the semi-structured interview. The following documents from the research universe were also surveyed: Summary table of Indicators /Action Plan/Political-Pedagogical Project 2022. After content analysis in the light of Laurence Bardin proposal, the following categories emerged: perception of quality, perception of participation and perception of participatory institutional self-assessment at the service of quality. The results indicate that there are still challenges for the school community: the understanding of the objectives of the Participatory Institutional Self-Assessment and its implementation, the presence and involvement of most families and the guarantee of the participation of babies and children.